2017
DOI: 10.5433/1679-0359.2017v38n5p2909
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus adsorption in soils under forest and savanna from Northern Amazon, Brazil

Abstract: Studies on maximum phosphorus adsorption capacity (MPAC) in soils from Roraima State and attributes that interfere with the magnitude of this characteristic are relevant and motivated this study. . P was analyzed in the supernatant for determining its adsorbed amount (P-rem). Adsorption values were fitted to the Langmuir isotherm in order to assess MPAC. Correlation tests were performed between MPAC and binding energy, pH, organic matter, clay, and CEC. MPAC values ranged from 14.50 to 527.93 mg kg −1 in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The synergistic effects between P and liming application on Pi BIC and Pi HID-0.1 (clayey soil), and on Pi HID-0.1 and Pi HID-0.5 (sandy soil) demonstrated the importance of both managements to increase P available in the soil, minimizing P immobilization in tropical soils. Pi HID-0.1 and Pi HID-0.5 are characterized as the most stable P pool in the soil, generally associated with Fe/Al (hydr)oxides present on clay surface (Matos et al 2017;Yang et al 2013;Abolfazli et al 2012;Cross and Schlessinger 1995). The study of Jalali and Ranjbar (2010) reported that P fractions associated with Fe/Al (hydr)oxides represent large amounts in calcareous soils, as well as in tropical soils under continuous cultivation as demonstrated by Teles et al (2017).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The synergistic effects between P and liming application on Pi BIC and Pi HID-0.1 (clayey soil), and on Pi HID-0.1 and Pi HID-0.5 (sandy soil) demonstrated the importance of both managements to increase P available in the soil, minimizing P immobilization in tropical soils. Pi HID-0.1 and Pi HID-0.5 are characterized as the most stable P pool in the soil, generally associated with Fe/Al (hydr)oxides present on clay surface (Matos et al 2017;Yang et al 2013;Abolfazli et al 2012;Cross and Schlessinger 1995). The study of Jalali and Ranjbar (2010) reported that P fractions associated with Fe/Al (hydr)oxides represent large amounts in calcareous soils, as well as in tropical soils under continuous cultivation as demonstrated by Teles et al (2017).…”
Section: Discussionmentioning
confidence: 95%
“…Phosphorus (P) availability has restricted crop growth in tropical acid soils due to the predominance of iron (Fe) and aluminum (Al) oxides in the soil fine fraction, which leads to P adsorption and P precipitation with Al and Fe (Vásconez and Pinochet 2018;Nascimento et al 2018;Matos et al 2017;Camargo et al 2013;). Both, P adsorption and precipitation, have negatively affected agricultural production in tropical conditions due to P unavailability (Barbosa et al 2018;Withers et al 2018;Yang et al 2012).…”
Section: Introductionmentioning
confidence: 99%